The Safety and Efficacy of Weighted Baseballs - Michael M Reinold; Leonard C Macrina (North American Sports Medicine Institute, 2021)
One of the most common methods of training to enhance pitching velocity is the use of weighted baseballs. As with anything else, the excitement and popularity often proceed our scientific understanding. While there is still a lot to learn, our understanding of the science and efficacy of weighted baseball training has grown in recent years. The purpose of this clinical viewpoint is to summarize our current scientific understanding.